Aplikasi Pengukuran Tahanan Pentanahan Untuk Pengamanan Tegangan Sentuh Dan Pelatihan Teknik Instalasi Listrik Bagi Masyarakat Desa Semparu Kecamatan Kopang Kabupaten Lombok Tengah - Agung Budi Muljono; I Made Ari Nrartha; Sultan Sultan; I Made Ginarsa; Sudi Mariyanto Al Sasongko (Jurnal Gema Ngabdi, 2019)
Electrical energy is one of the vital needs that cannot be separated from the needs of everyday life. In energy use, a protection in the electrical installation system is needed for safety related to electricity, among others, to avoid the danger of touch voltage. Protection intended in this electricity system is to provide a protection system to realize reliable and safe conditions, both for workers and the general public, in accordance with General Standard of Electrical Instalation PUIL 2011 and the Electricity Law of 2002. Activities are carried out in Semparu Village, Kopang District, Central Lombok Regency, through counseling, training and direct measurement of detainee detention. With the aim of providing installation techniques according to standards and grounding systems for security of installation of touch stresses that are harmful to human safety. Based on the results of the evaluation, the mean pretest score of 39.375 was 65.3 in the posttest mean or there was an increase in basic understanding and further participants by 72%. The results of the grounding resistance test at the village office in Semparu with the earth tester obtained a mean yield of 4.2 Ω with a post depth of 1.5 m with the wet soil type of the former rice field already in accordance with the PUIL 2011 standard which is smaller than 5 Ω